'Seeing everything in a new light': Edinburgh International Book and Arts Festival Diary 2020. Issue 1 (February 2021) - Relich, Mario
Abstract : A personal review of the 2020 Edinburgh International Festivals, much reduced and mostly online due to Covid-19.